Systemic Factors Influence the Prognosis of Diabetic Macular Edema after Pars Plana Vitrectomy with Internal Limiting Membrane Peeling. (December 2013) - Yamada, Yoshihisa; Suzuma, Kiyoshi; Ryu, Michi; Tsuiki, Eiko; Fujikawa, Azusa; Kitaoka, Takashi
Abstract Purpose/Aims: To evaluate the prognostic factors for the best corrected visual acuity (BCVA) and central subfield macular thickness (CSMT) after vitrectomy with internal limiting membrane (ILM) peeling for diabetic macular edema. Materials and Methods: A total of 44 eyes of 35 patients who had undergone vitrectomy with ILM peeling between March 2008 and September 2009 were examined. The relationships between preoperative systemic or ocular factors and BCVA or CSMT were evaluated before and at 6 months after the surgical procedure. Results: Mean logarithm of the minimum angle of resolution improved from 0.74 ± 0.35 (mean ± SD) preoperatively to 0.55 ± 0.4 at 6 months postoperatively (p = 0.001). There was a significant improvement of the CSMT from 482 ± 116 μm before the operation to 355 ± 126 μm 6 months after the operation (p < 0.0001). The preoperative CSMT was significantly thicker with ischemic disease (p = 0.0016). Preoperative BCVA was significantly lower when subfoveal hard exudate was present (p = 0.0005). At the 6-month follow-up, CSMT was significantly thicker when there was a higher glycosylated hemoglobin (p = 0.008). BCVA at the 6-month follow-up was significantly lower in the group without any diabetes treatment history (p = 0.0075) prior to the diagnosis of diabetic retinopathy. Conclusions: While BCVA and CSMT were associated with ocular factors before surgery, they were associated with glycemic control postoperatively. Glycemic control may be important for retinal thickness after ocular surgery.